Optimalisasi Pemanfaatan Tanah Aset Pemerintah Kota Semarang di Kecamatan Banyumanik - Sundari, Minik; Ma'rif, Samsul (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Activity growth in Semarang City has lead to the intensification of land use in the city centers as well as expansion of the built up area at the fringes. However, there are still several pieces of empty local government land asset which have not been utilized and have remained barren. This study aimed to find the optimum form of utilization of such asset by examining 6 pieces of land in Banyumanik District, Semarang City which was categorized as barren land asset by the local government. In actuality, such lands are prone to conflicts in both its ownership and utilization. This study employed qualitative approach in identifying the characteristics of the observed land and quantitative approach in finding the alternatives for utilization of such land asset through AHP analysis. This study found that the optimum form of utilization of empty land asset in high-growth areas are (1) be rented to other parties or (2) be used for plantation and freshwater fisheries, while for lands in low-middle growth areas, the optimum form of re-utilization included (1) utilization for public facilities, and (2) plantation and farming.